Analisis Pengaruh Formulasi dan Bahan Penghancur terhadap Waktu Hancur Tablet - Cheina Nazerina Yoshi; Luthfia Raisah Ahyati; Nur Rifa Ashya; Nurul Hasni Julianti; Yenni Hafizah; Nor Latifah (Jurnal Ventilator, 2024)
Tablets are solid preparations consisting of active drug substances and fillers. The purpose of adding a crushing agent is to reduce the pressure that occurs in making tablets, especially during the tablet release process which begins with breaking it. This study aims to investigate a number of components that influence the disintegration or breaking time of tablets, such as the choice of disintegrating agent, excipient composition, and environmental conditions such as pH and temperature. The research results show that choosing the right disintegrating agent, such as starch or starch, can accelerate tablet disintegration by increasing its ability to swell in liquid. Faster disintegration times can be achieved through the addition of appropriate disintegrating agents and optimization of tablet formulation, which ultimately supports increased drug therapeutic effectiveness. The methodology employed in this analysis is predicated on a survey of the literature on electronic data sources. Based on existing literature, starch or starch granules have the ability to swell up when exposed to water, amylose also has similar properties, namely that they both function as disintegrating agents. Concluded that amylum or starch derived from various plants is effectively utilized as a tablet disintegrating agent due to its superior to interact with water, but also because the evaluation results almost all meet the established standards.